MAGMATISMO GRANITÓIDE DAS SUÍTES INTRUSIVAS SANTA CRUZ E ALVORADA NO DOMÍNIO TECTÔNICO CACHOEIRINHA, SW DO CRÁTON AMAZÔNICO - de Araújo, L. M. B.; Godoy, A. M.; Ruiz, A. S.; Zanardo, A.; Manzano, J. C.; da Silva, J. A. (Geochimica Brasiliensis, 2012)